2007
DOI: 10.1007/s10661-007-9852-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and origin of the hydrogen sulphide spring water from the Split spa (Southern Croatia)

Abstract: The objective of this paper is to study the hydrological characteristics and origin of the hydrogen sulphide spring water from the Split spa in Southern Croatia in 1987, 1988 and 2003. This paper presents the results of monitoring the content of chlorides and hydrogen sulphide as well as the temperature of the hydrogen sulphide spring water. Since the hydrogen sulphide content during the dry periods significantly differs from the hydrogen sulphide content during rainy periods, this paper also compares the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Furthermore, although measurement of H 2 S levels in biological specimen is technically difficult , concentrations of more than 100 μmol/l have been detected in synovial fluid of patients with RA . Of note, sulphur concentration in thermal waters used for therapy of rheumatic and other diseases usually ranges between 0.1 and 0.2 mmol/l but in some springs may even exceed 1 mmol/l, e.g . in the spa Vienna‐Oberlaa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although measurement of H 2 S levels in biological specimen is technically difficult , concentrations of more than 100 μmol/l have been detected in synovial fluid of patients with RA . Of note, sulphur concentration in thermal waters used for therapy of rheumatic and other diseases usually ranges between 0.1 and 0.2 mmol/l but in some springs may even exceed 1 mmol/l, e.g . in the spa Vienna‐Oberlaa.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the results obtained in vitro combined to the in vivo histological ones, the design of a clinical trial with sulfur-rich waters involving an adequate number of patients appears as reasonable. Spring water is classified as sulfurous when it contains 41 mg/l of H 2 S. Often sulfide concentration in such natural waters varies from 0.5 to 20 mg/l, 44 which makes balneotherapy an effective option for these patients. Considering that we had previously demonstrated that sulfurs have subset-specific toxicity on CD8 þ lymphocytes, 26 another major player in the complex pathophysiology of psoriasis, we believe that sufficient scientific …”
Section: Resultsmentioning
confidence: 99%
“…With a temperature at the source of 47.6 ± 0.5 °C, the thermal spring water at Contursi Terme can be classified as hyperthermal (Štambuk-Giljanović 2008;Quattrini et al 2016). Monthly water samples were taken from the pool of the thermal springs during the sampling period.…”
Section: Sampling Sitementioning
confidence: 99%